DESAIN PRIMER GEN PENGKODE RNA DEPENDENT RNA POLIMERASE (RdRp) UNTUK DETEKSI SARS COV2 DENGAN MENGGUNAKAN REAL TIME POLYMERASE CHAIN REACTION - Fusvita Merdekawati; Betty Nurhayati (Poltekkes Kemenkes Bandung, 2023)
Corona virus or severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is a virus that attacks the respiratory system. Disease caused by infection with this virus is called Corona Virus Disease 19 (COVID-19). Infection due to SARS-CoV-2 was declared by the World Health Organization (WHO) as a pandemic. Detection of infection due to SARS COV2 is carried out using Real Time Polymerase Chain Reaction by detecting the viral RNA sequence as the gold standard. One of the targeted viral genes is RNA-dependent RNA polymerase (RdRp). Detection using PCR consists of nucleic acid isolation, DNA amplification using qPCR and amplification curve reading. Testing for SARS-COV2 using molecular techniques uses several reagents that have been recommended by WHO. These reagents are special and close system where the master mix reagent component has been mixed with the primer so you cannot use reagents in general. Primer is an important component in a molecular detection system. Primer functions as a barrier for the target DNA fragment to be amplified. Each target fragment requires a pair of primers that match the target DNA. This primer needs to be designed to achieve a high success rate in detecting SARS-COV2. In silico primer design will make it easier to obtain good primers for the amplification of gene fragments. Based on the research results, the forward primer sequence was ACCGTAGCTGGTGTCTCTAT and the reverse primer sequence was GTGCCAACCACCATAGAATTTG. Furthermore, an in vitro detection process was carried out to test the success of the primer in forming the desired product. Based on the research results, the primer can stick to the DNA template as evidenced by the formation of an amplification curve with a CT value of 21,627 with optimal PCR conditions through the following stages: Reverse transcription at 37°C, 15 minutes, 1 cycle, Inactivation of Reverse transcriptase and Activation of DNA Polymerase at 95°C for 10 minutes, 1 cycle, Denaturation at 95°C for 10 seconds, 40 cycles, annealing at 56°C for 10 seconds 40 cycles. Followed by the extension stage at 72°C for 30 seconds for 1 cycle.